Aplicación de tres tipos de fertilizantes en Ochroma pyramidale Cav. (balsa) en el Cantón Mocache, Provincia de Los Ríos. - Carrera Cruz, Ramón Cristóbal (2012)
The present research was carried out in the Julita farm, property of Mr. Ramón Carrera Cruz, in The banks sector, Canton Mocache, Los Ríos county. The farm is to an height of 80 masl. This area belongs to the Tropical Humid Forest (bh-T) ecological formation with an annual half precipitation of 1223 mm and temperature average of 24,6ºC. The objectives of this investigation were: to estimate the growth, of the diameter, basal area, total height and volume of the raft, in the canton Mocache and to determine the effect of the fertilization on the growth of the raft. The effect of three types of fertilizers and a witness on the growth of the raft was evaluated. The experimental parcels were established at a random blocks design with three repetitions. At the twelve months of the application of the fertilizers, the DAP, total height, basal area, volume and the height of insert of branches didn't present significant differences. These results suggest that the soils of the area where the essay was carried out are fertile that they allow a good growth of the raft. It is recommended to test other fertilizers of slow decomposition and to compare the results in raft plantations in the area of Mocache.